Administration of extract Salix tetrasperma combined with extract of turmeric and neem to improve eggs quality of chicken reared under heat stress - Sugito, .; Hambal, M.; Isa, M.; Nurliana, .; Delima, D. (Indonesian Animal Sciences Society, 2015)
Quality of eggs might decrease when hens under heat stress. A further study found that a specific plant extracts could reduce the impacts of heat stress. The aim of this study was to determine effects of Salix tetrasperma plant extract in combination with extract of turmeric and neem to improve egg quality and productivity of laying hens under heat stress. Sixty laying hens strain Isa Brown of 6 months old were used and reared in individual cages. The feed and drinking water were supplied ad libitum. This study was conducted in a completely randomized design with five treatments (two controls and three treatments) and each treatment consisted of 12 replication. Treatment consisted of with (KP) and without (KP) commercial anti-stress supplement. Formulations of extract were S. tetrasperma 1.000 mg / l water (EJ), S. tetrasperma 1.000 mg / l + Turmeric 250 mg / l + neem 250 mg / l (EJ+K1), and S. tetrasperma 1.000 mg / l + Turmeric 500 mg / l + neem 500 mg / l drinking water (EJ+K2). The hens were exposed to heat stress for 5 hours per day at a temperature range of 34.0Â±1.0Â°C. Supplements were dissolved in drinking water and were given for 30 days in the morning and noon. Results showed that a single extract of S. tetrasperma or the combination of an extract of turmeric and neem were significantly increased thickness of eggshell (P<0.05), but did not affect color of egg yolk, height albumin, egg weight, and HU value. Extract of S. tetrasperma combined with turmeric and neem extract dissolved in drinking water for 30 days in laying hens reared under heat stress could not improved quality of the eggs, but may increase thickness of the egg shell and cause decreased water consumption. Key Words: Egg Quality, Salix tetrasperma, Turmeric, Neem, Heat Stress